Exploration of Dragonfly Diversity in Sendang Gile Waterfall and its Development as Local Potential-Based Biology Learning - Susilawati, Nur; Ilhamdi, Mohammad Liwa; Artayasa, I Putu (Jurnal Biologi Tropis, 2026)
This study aimed to inventory the dragonfly species inhabiting the Sendang Gile Waterfall area, evaluate their diversity, and develop the findings into a local biodiversity-based biology learning resource for senior high school students. A descriptive exploratory approach was employed using a sweep net sampling method along three observation transects. Species diversity was analyzed using the Shannon–Wiener diversity index (H′), evenness index (E), and dominance index (C). The research findings were subsequently developed into a biology booklet and evaluated through expert validation involving material and media specialists. A total of 364 dragonfly individuals representing 12 species from five families were recorded. Euphaea lara lombokensis was the most abundant species, accounting for 119 individuals. The overall Shannon–Wiener diversity index (H′ = 1.81) indicated a moderate level of species diversity, accompanied by a relatively balanced species distribution and low dominance. The developed booklet obtained an average validation score of 90.09%, indicating that it was highly valid and suitable for educational use. These findings demonstrate that the Sendang Gile Waterfall area supports a moderately diverse dragonfly community and that the developed booklet can serve as an effective local biodiversity-based learning resource for biology education in senior high schools.